2016
DOI: 10.1016/j.jconrel.2016.07.050
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-associated oral delivery: Mechanisms and analysis of oral absorption enhancement

Abstract: The majority of newly discovered oral drugs are poorly water soluble, and co-administration with lipids has proven effective in significantly enhancing bioavailability of some compounds with low aqueous solubility. Yet, lipid-based delivery technologies have not been widely employed in commercial oral products. Lipids can impact drug transport and fate in the gastrointestinal (GI) tract through multiple mechanisms including enhancement of solubility and dissolution kinetics, enhancement of permeation through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 191 publications
0
40
0
1
Order By: Relevance
“…However, oral absorption of a lipid-based formulation can be readily affected by dietary intake, lipid digestion, lipid emulsifiers such as bile salts, and dilution effect in and the pH of GI fluids. 27 In addition, many organic solvents were used to prepare the lipid/drug conjugate. However, when a drug is conjugated with a cell recognition moiety such as a International Journal of Nanomedicine 2018:13 submit your manuscript | www.dovepress.com…”
Section: Introductionmentioning
confidence: 99%
“…However, oral absorption of a lipid-based formulation can be readily affected by dietary intake, lipid digestion, lipid emulsifiers such as bile salts, and dilution effect in and the pH of GI fluids. 27 In addition, many organic solvents were used to prepare the lipid/drug conjugate. However, when a drug is conjugated with a cell recognition moiety such as a International Journal of Nanomedicine 2018:13 submit your manuscript | www.dovepress.com…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Consequently, many of these compounds come along with limited and often highly variable bioavailability (BA) and place a significant burden on drug development. [3] However, for many of these APIs, particularly for BCS class II compounds, there is a good chance of enhancing bioavailability and also decreasing its variability by utilizing drug delivery strategies ensuring that the API is readily and completely dissolved in the lumen of the upper gastrointestinal (GI) tract.…”
Section: Introductionmentioning
confidence: 99%
“…SBO and FO) are used in formulation of lipid-based drug delivery systems [19,[31][32][33][34][35], and lipids can also impact drug absorption when drug is coadministered with food-associated lipid. The mechanism and analysis of drug delivery involving lipids have been reported by our lab and others illustrating that lipid-based formulations have great potential for facilitating effective hydrophobic oral drug delivery [36,37].…”
Section: Use Of Lipids For Oral Drug Deliverymentioning
confidence: 87%
“…The composition of simulated fluids containing model bile micelles at fed concentration is summarized in Table 2 [36]. The fed state solution was prepared for all lipid digestion and drug dissolution studies reported in this thesis as 4X concentration to allow room for dilution to a 1X concentration model lipid and lipase.…”
Section: Preparation and Characterization Of Emulsionmentioning
confidence: 99%